2015
DOI: 10.1021/acs.jafc.5b01931
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation and Structure–Anti-inflammatory Activity Relationships of Cembranoids from Cultured Soft Corals Sinularia sandensis and Sinularia flexibilis

Abstract: New cembranoids 4-carbomethoxyl-10-epigyrosanoldie E (1), 7-acetylsinumaximol B (2), diepoxycembrene B (6), dihydromanaarenolide I (8), and isosinulaflexiolide K (9), along with 11 known related metabolites, were isolated from cultured soft corals Sinularia sandensis and Sinularia flexibilis. The structures were elucidated by means of infrared, mass spectrometry, and nuclear magnetic resonance techniques, and the absolute configurations of 1, 4, 9, and 15 were further confirmed by single-crystal X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…829 X-ray studies were used to determine the complete structural and stereochemical characterization of sarcophelegan A 1164, 825 cembranoid 1173 and isosinulaexiolide K 1177. 829 X-ray studies were also used to conrm the structures and conguration of previously reported cembranoids sarsolilide B (Sarcophyton trocheliophorum) 826,830 pukalide (Leptogorgia alba) 831 and dendronpholide F (Dendronephthya sp.) 829,832 The trivial name epoxynephthenol assigned to 1150 (ref.…”
Section: Cnidariansmentioning
confidence: 99%
“…829 X-ray studies were used to determine the complete structural and stereochemical characterization of sarcophelegan A 1164, 825 cembranoid 1173 and isosinulaexiolide K 1177. 829 X-ray studies were also used to conrm the structures and conguration of previously reported cembranoids sarsolilide B (Sarcophyton trocheliophorum) 826,830 pukalide (Leptogorgia alba) 831 and dendronpholide F (Dendronephthya sp.) 829,832 The trivial name epoxynephthenol assigned to 1150 (ref.…”
Section: Cnidariansmentioning
confidence: 99%
“…Sinulariolide was prepared from the extract of cultured-type soft coral Sinularia flexibilis, following the previously published protocol [40,41] …”
Section: Materials and Antibodiesmentioning
confidence: 99%
“…In some plants, cubitene was detected by gas chromatography–mass spectrometry (GC/MS) from their volatile oils [6]. In the aforementioned three sources, cubitanoids were usually found in company with cembranoids [1], which represent a large group of compounds in soft coral [7,8,9,10]. The origin of cubitanoids was speculated to be associated with the co-occurring cembranoids based on a photochemical interconversion [4].…”
Section: Introductionmentioning
confidence: 99%